Reciprocal activation between M1 macrophages and trophoblasts through CXCL9/STAT1/ZEB1/CCL2 axis promotes recurrent spontaneous abortion - Yan, Sisi; Wang, Xiang; Wu, Qiuji; Ding, Jinli; Qiu, Hui (Frontiers in Immunology, 2025)
BackgroundThe crosstalk between macrophages and trophoblasts plays a crucial role in the development and progression of recurrent spontaneous abortion (RSA). Although M1 macrophages (M1-Mφ) are known to accumulate in RSA decidual tissues, their direct functional impact on trophoblasts remains poorly characterized.MethodsWe established an M1-Mφ-trophoblast coculture system to investigate this interaction. CXCL9 expression was quantified in clinical samples and cell lines using qPCR, ELISA, and immunofluorescence. The migration and invasion capacities of trophoblasts were evaluated through wound healing and Transwell assays. A series of rescue experiments were conducted to uncover the underlying mechanism. Finally, an in vivo animal model was carried out to validate the corresponding functions of the CXCL9-related axis.ResultsOur results revealed that M1-Mφ inhibited the migration and invasion of trophoblasts by releasing CXCL9. The expression of CXCL9 in decidual tissues was significantly increased in RSA samples compared to healthy controls. Mechanistically, CXCL9 activated the CXCR3-dependent JAK/STAT1 signaling pathway. Activated STAT1 induced transcriptional upregulation of ZEB1 via IRF1, which in turn promoted the release of CCL2 to enhance macrophage recruitment. In vivo, inhibition of CXCL9 reduced embryo resorption in LPS-induced abortion mice, attenuated macrophage infiltration, and restored trophoblast migration and invasion.ConclusionOur work identifies a novel mechanism by which M1-Mφ regulate trophoblast migration and invasion through the CXCL9/STAT1/IRF1/ZEB1 axis, which in turn leads to the release of CCL2 that promotes macrophage infiltration in RSA, highlighting a new form of crosstalk between macrophages and trophoblasts.